Understanding the intrinsic and extrinsic factors in financial literacy of the Orang Asli in Malaysia - Ali, Mazurina Mohd; Muhammad, Kamaruzzaman; Ghani, Erlane K; Ilias, Azleen; Tarmezi, NurAzrin (Nurture, 2024)
Purpose: This study aims to examine the financial literacy of the indigenous people known as Orang Asli in Malaysia and examines the intrinsic and extrinsic factors that may influence financial literacy among the Orang Asli in Banting, Selangor, Malaysia. Four factors are chosen namely, financial attitude and financial knowledge which represent the intrinsic factors and parental socialization and peer influence which represent the extrinsic factors. Design/Methodology/Approach: The researchers approached the village chief of the Orang Asli in Kampong Tadom, Banting to seek his assistance in conducting the questionnaire survey. The researchers came to the village and distributed the questionnaires to 102 Orang Asli. Findings: According to the findings of this study, only financial knowledge influences the financial literacy of Orang Asli in Banting, Selangor. As a result, JAKOA can implement a few tactics to improve their financial understanding and their financial literacy such as delivering financial education programmes and teaching financial awareness at an early age. However, this factor contributes 60% to the financial literacy of the Orang Asli despite the fact that only financial knowledge significantly influences the financial literacy of the Orang Asli. Practical Implication: The findings of this study provide insights and recommendations to enhance financial education initiatives targeted specifically at Malaysian Orang Asli. Contribution to Literature: The findings of this study contribute to the existing literature on the financial literacy of the Orang Asli.